INTEGRASI REMEDIASI MISKONSEPSI TENTANG MOMENTUM DAN IMPULS MENGGUNAKAN MODEL ECIRR INTEGRASI REMEDIASI MISKONSEPSI TENTANG MOMENTUM DAN IMPULS MENGGUNAKAN MODEL ECIRR - Jamilah, Jamilah; Silitonga, Haratua Tiur Maria; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purposed of this research was to examine the effectiveness of integrated remediation misconception using ECIRR model to reduce the number of students misconceptions and to improve learning achievment about momentum and impulse at tenth grade of SMA Negeri 7 Pontianak. This research was quasy experimental with pretest-posttest control group design. The samples were determined by intact group techniqu based on homogeneous data, and obtained X MIA 1 as an experimental class, and X MIA 2 as a control class. The research instruments included 15 diagnostic test and 4 learning achievment test. Based on McNemar tes, the students conceptions changed significantly with ?2score of experimental class (70,78) and the control class (79,63). Based on U Mann Whitney test showed that value asymptote significance for the two-tailed test is 0,056 above 0.05 which means there were no differences on the learning achievment between the experimental class and the control class. The effect size integrated remediation misconceptionto to reduce the number of students misconceptions ((0,7016) and to improve learning achievment (d =4,62) was high. Thus, the use of integrated remediation misconception was effective to reduce the number of students misconceptions and to improve learning achievment about momentum and impulse. Keywords: ECIRR model, Integrated remediation misconception, Momentum and Impulse.